Simulasi Penyebaran dan Persentase Fatalitas Oleh Gas SO2 dan CO2 Hasil Pembakaran PLTU Independent Power Producer (IPP) Lombok Timur (50 MW) Dengan Low Rank Coal Menggunakan Model Gaussian - Shafwan Amrullah; Sopyan Ali Rohman; Lalu Heri Rizaldi (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
The Sembelia Steam Power Plant is located in East Lombok, West Nusa Tenggara and is managed by PT. Lombok Energy Dynamic uses the light coal until 200,000 tons per year. This case can be the environmental pollution. This study aims to calculate the SO2 and CO2 exhaust gases into the environment by the simulation as well as included the %fatality due to coal combustion of the The Sembelia Steam Power Plant with the model of Gaussian. This research was carried out by calculating the SO2 and CO2 concentrations released concentration. At the end of these project, we calculated the SO2 and CO2 released by the dispersion potential and %fatality at four points around it. The result of this research showed that the dispersion mass of SO2 dispersion was 0.096 kg per second (with distance of 2,000 to 46,000 m). This result showed that the increases (6.876x10-46 ppm to 1.276x10-5 ppm), and then showed that the decreases to 0 ppm. % Fatality in this study is 0%. The potential of CO2 dispersion with an outgoing mass of 8,252 kg/second increased (2,000-58,000 m) with a concentration of 62.47x10- 63 ppm to 7.9x10-4ppm. In the other hand, the concentration of CO2 was reduced to 0 ppm. In the end of this study showed that %fatality by the CO2 released is 0%, and the calculation of dispersion at four points around the The Sembelia Steam Power Plant is safe from the SO2 and CO2 dispersion.